Mitochondrial trifunctional protein deficiency as a polyneuropathy etiology in childhood - Uzun, Özlem Ünal; Çavdarlı, Büşra; Karalök, Selen (The Turkish Journal of Pediatrics, 2021)
Background. The mitochondrial trifunctional protein (MTP) is a multienzyme complex of the fatty acid betaoxidation cycle. Mitochondrial trifunctional protein deficiency (MTPD), a rare condition that leads to failure of converting certain fats to energy is characterized by decreased activity of three enzymes in the enzyme complex. Signs and symptoms of MTPD may present during infancy or later in life; those that begin after infancy include hypotonia, muscle pain, rhabdomyolysis, and peripheral neuropathy. We report a Turkish boy diagnosed with MTPD after being investigated for polyneuropathy of unknown origin since infancy. Case. A 5.5-year-old male patient was admitted to our clinic with complaints of weakness in the arms and legs, physical inactivity compared to his peers, fatigue, weakness and, difficulty in climbing stairs since infancy. Electroneuromyography (ENMG) analysis showed moderate symmetric distal sensorimotor and axonal neuropathy. On the background of chronic polyneuropathy, the patient had acute relapsing episodes with progressively worsening severity in the follow-up period until 12.5 years of age. Whole exome sequencing (WES) was performed in the patient and, revealed that the patient had a homozygous c.1390G > A (p.Gly464Ser) pathogenic variant of the HADHB gene. Although rhabdomyolysis is a well defined accompanying clinical feature of MTPD, it was not present in our patient who only had worsening muscle weakness during attacks. Conclusion. On the background of chronic polyneuropathy and acute relapsing episodes triggered by fasting or illnesses and rhabdomyolysis physicians should suspect disorders of the fatty acid beta-oxidation cycle.
Keywords: HADHB gene; fatty acid oxidation disorder; mitochondrial trifunctional protein deficiency; polyneuropathy